2015
DOI: 10.1037/cou0000077
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic microaggressions, traumatic stress symptoms, and Latino depression: A moderated mediational model.

Abstract: Although ethnic microaggressions have received increased empirical attention in recent years, there remains a paucity of research regarding how these subtle covert forms of discrimination contribute to Latino mental health. The present study examined the role of traumatic stress symptoms underlying the relationship between ethnic microaggressions and depression. Further, ethnic identity and general self-efficacy were tested as moderators between the ethnic microaggressions and traumatic stress link. Among a sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
89
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(109 citation statements)
references
References 58 publications
10
89
1
1
Order By: Relevance
“…Passive harm, a subtle and paternalistic form of ethnic discrimination, was reported most frequently in our sample of Russian immigrants, followed by everyday discrimination and active harm. This frequency distribution is similar to other studies which reported that the frequency of more subtle forms of discrimination has increased over time, whereas blatant forms have become less frequent [e.g., (16,101)]. We found that everyday discrimination was prevalent in our sample; this fits the notion that discrimination remains a pervasive factor in housing, education, employment, and health care (30,(102)(103)(104).…”
Section: Discussionsupporting
confidence: 90%
“…Passive harm, a subtle and paternalistic form of ethnic discrimination, was reported most frequently in our sample of Russian immigrants, followed by everyday discrimination and active harm. This frequency distribution is similar to other studies which reported that the frequency of more subtle forms of discrimination has increased over time, whereas blatant forms have become less frequent [e.g., (16,101)]. We found that everyday discrimination was prevalent in our sample; this fits the notion that discrimination remains a pervasive factor in housing, education, employment, and health care (30,(102)(103)(104).…”
Section: Discussionsupporting
confidence: 90%
“…These racial slights may be perceived as harmless, but they are considered a form of everyday discrimination and racism that induce emotional and traumatic stress responses in those afflicted. In a study of Latinos, traumatic stress responses were the mechanisms by which microaggressions contributed to symptoms of depression and anxiety [ 44 ]. Discrimination is also associated with increased anxiety, affective, and substance abuse disorders among African Americans, Hispanic Americans, and Asian Americans [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is also strong evidence that microaggressions lead to elevated levels of depression and trauma among marginalized communities . For example, in a study of undergraduate students, depression and suicidal ideation were linked to racial microaggressions …”
Section: Microaggressions ‐ Examples and Impactmentioning
confidence: 99%